Cost evaluation in design for end-of-Life of automotive components - Catherine Anthony; Wai M. Cheung (Journal of Remanufacturing, 2017)
The European Union implemented the End-of-Life Vehicle directive to deal with an estimated 6 million end-of-life vehicles each year. Existing literature describe the processes to deal with the waste at end-of-life of different products but there is a lack of information on the costing of these options. These costs remain a concern to automotive manufacturers. This paper therefore reports the end-of-life costs of vehicle components and also demonstrates how these costs can be predicted at the design stage. The proposed approach should help to decide whether the automotive parts are viable for remanufacture, refurbishment, recycling, or disposal from an economic perspective. Two different automotive parts have been selected as case studies to validate the approach. Assumptions were made during the development of the technique and based on the results, the proposed approach could potentially provide vehicle manufacturers a method of estimating the cost of end-of-life recovery processes of vehicle components.
Keywords: 650; End-of-life vehicle; Remanufacture; Refurbish; Recycle; Disposal; ELV; EoL costs